Iraq in Pictures - Teta, Jon A. (New York Sterling Publishing Co. Inc., 1972)
Photographs and text introduce the geography, history, government, people, and economy of Iraq, "the cradle of civilization."
Include Maps and Illustrations
Keywords: Iraq